Georgian Educational Schools In Athens (The End Of The 20th Century And The Beginning Of The 21st) - Kukchishvili, Maia (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2016)
Georgian educational centres founded in Greece have historical roots. In our article we have just discussed the activities of some Georgian educational centres from the end of the 20th century and the beginning of the 21st. These centres are as follows: Georgian institute at Athens, CAUCASUS-Cultural Centre, Vakhtang VI Georgian Sunday-school, Georgian-Greek cultural and educational centre “Armazi”. All these schools are following different curriculums. Their aim is to connect Georgians, keep the national identity in the future generations, popularize Georgian culture among the Georgian population living in Greece and facilitate the integration of Georgian immigrants in Greek society. Georgian educational organizations comprise Sunday-schools, Georgian library, the ensembles of Georgian music and dance, theatres and sections of different fields, children center with pre-school program, etc. Our nationals in Athens actively participate in Greek cultural, public and political affairs.